2000
DOI: 10.1007/s004390000267
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of 33 single nucleotide polymorphisms (SNPs) in 29 candidate genes for bronchial asthma: positive association of a T924C polymorphism in the thromboxane A2 receptor gene

Abstract: Although intensive studies have attempted to elucidate the genetic background of bronchial asthma (BA), one of the most common of the chronic inflammatory diseases in human populations, genetic factors associated with its pathogenesis are still not well understood. We surveyed 29 possible candidate genes for this disease for single nucleotide polymorphisms (SNPs), the most frequent type of genetic variation, in genomic DNAs from Japanese BA patients. We identified 33 SNPs, only four of which had been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 18 publications
7
75
2
Order By: Relevance
“…Conflicting results about the genetic alteration of TBXA2R in the involvement of asthma have been reported in an Asian population (13)(14)(15). Genetic alteration of CRTH2 has been correlated to allergic asthma in African-American and Chinese populations (18), but not in a Japanese population (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results about the genetic alteration of TBXA2R in the involvement of asthma have been reported in an Asian population (13)(14)(15). Genetic alteration of CRTH2 has been correlated to allergic asthma in African-American and Chinese populations (18), but not in a Japanese population (19).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kim et al (14) showed that the TBXA2R polymorphism was not associated with asthma susceptibility and the clinical parameters of asthma. In a Japanese population, Unoki et al (15) found that the synonymous +924T>C polymorphism in the TBXA2R gene was associated with a diagnosis of asthma in adult asthmatic patients, but not in children. However, their claim of an involvement of TBXA2R in Japanese asthmatics does not seem to be substantiated by their data (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…There are several SNPs in TRAIL, including 4 SNPs in the 5ꞌ-regulatory region, 2 SNPs within exons, and 5 SNPs in the 3ꞌ-untranslated region (3ꞌ-UTR) (Unoki et al, 2000;Wang et al, 2000;Gray et al, 2001). Generally, 3'-UTR has wide-range influences on gene regulation (Zhang et al, 2004;Watanabe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs were genotyped by allele-specific oligonucleotide (ASO) hybridization as described previously (Unoki et al 2000). Allele-specific probes ( 32 P-labeled 13-to 17-mers) of 5Ј-TACGCCCTCGGGG-3Ј or 5Ј-TACGCC GTCGGGG-3Ј for C(IVS ϩ 8)G of DUSP1, and 5Ј-GGGTGGCTGCTCC-3Ј or 5Ј-GGGTGGTTGCTCC-3Ј for C(-67T) of BTG1, were hybridized at 37°C to the polymerase chain reaction (PCR) products on the membranes and washed in 6 ϫ standard saline citrate (SSC) at 42°C (DUSP1) or at 46°C (BTG1) according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%